Audit of transfusion practice during burns surgery at the Red Cross War Memorial Children's Hospital - Spies, Anri (Department of Anaesthesia, 2018)
Rationale: Major burn surgery can be associated with significant blood loss, often requiring transfusion of blood products. In an effort to decrease aforementioned blood loss, various blood conservation strategies have been developed, rendering older formulae to predict intraoperative blood loss ineffective and outdated. Currently there are no clear guidelines on when to transfuse burn victims but, the trend is towards employing a more conservative transfusion practice in an attempt to reduce transfusion related complications. The predicament has become one of containing cost by not ordering blood unnecessarily and/or excessively, versus putting a patient at risk by not having blood available when he or she needs it. A guideline, based on haemoglobin and extent of surgery, was drawn up at the Red Cross War Memorial Children's Hospital in an effort to rationalise preoperative blood ordering. The aim of this audit was to assess how well the implemented guideline was adhered to, and how accurately the guideline predicted the need to have blood products available in theatre during burns surgeries of varying extent. Methods: After a guideline, based on expert opinion, had been drawn up and implemented, a prospective audit of practice was done from April 2014 to June 2015. Two hundred separate burn surgeries were audited. Data collected included haemoglobin levels, extent of surgery, pre-and intra-operative instructions to blood bank, and whether patients were transfused. Pre-operative instructions were compared to the guideline to test adherence, and to the ultimate need for blood to test accuracy. Additional data recorded were the adherence to surgical plan (extent of surgery). Results: Five of the 200 cases were excluded due to incomplete data, leaving 195 cases. Blood was ordered according to the guideline in 131 (67.2%) cases. There were two groups where adherence was particularly poor. In these patients the guideline suggested that only a group and screen was necessary - a category for which it would also be difficult to assess how accurately the guideline predicts the need for blood. After excluding these two groups, the preoperative instructions to the blood bank were appropriate in 119 (94.4%) of the 126 cases where the guideline was followed. Blood was ordered preoperatively in 83 of the 195 cases, but only used in 50 cases (60.2%). Of the 33 cases where blood was not used, 23 cases were not in keeping with the guideline. In 50 (83%) of the 60 cases where blood was ordered according to the guideline, it was appropriate. The performed surgery proceeded as planned in 162 (83.1%) cases. Discussion: Blood transfusion exposes the recipient to transfusion-related risks and is expensive. In an attempt to avoid these risks there has been a trend towards conservative transfusion practices. It has been shown to be cost effective and safe to employ a restrictive transfusion practice during major paediatric burn surgery. During our study period one unit of blood cost R1096,00 and a group and screen R172,00. Significant savings could therefore be incurred if blood is ordered according to the proposed guideline. Conclusion: This audit confirmed that the guideline is an appropriate one to use for preoperative ordering of blood products for burns surgery at the Red Cross War Memorial Children's Hospital.